Associations between an international COVID-19 job exposure matrix and SARS-CoV-2 infection among 2 million workers in Denmark - Sophie van der Feltz; Vivi Schlünssen; Ioannis Basinas; Luise M Begtrup; Alex Burdorf; Jens PE Bonde; Esben M Flachs; Susan Peters; Anjoeka Pronk; Zara A Stokholm; Martie van Tongeren; Karin van Veldhoven; et al. (Scandinavian Journal of Work, Environment & Health, 2023)

(untitled)
OBJECTIVES: This study investigates the associations between the Danish version of a job exposure matrix for COVID-19 (COVID-19-JEM) and Danish register-based SARS-CoV-2 infection information across three waves of the pandemic. The COVID-19-JEM consists of four dimensions on transmission: two on mitigation measures, and two on precarious work characteristics. METHODS: The study comprised 2 021 309 persons from the Danish working population between 26 February 2020 and 15 December 2021. Logistic regression models were applied to assess the associations between the JEM dimensions and overall score and SARS-CoV-2 infection across three infection waves, with peaks in March–April 2020, December–January 2021, and February–March 2022. Sex, age, household income, country of birth, wave, residential region and during wave 3 vaccination status were accounted for. RESULTS: Higher risk scores within the transmission and mitigation dimensions and the overall JEM score resulted in higher odds ratios (OR) of a SARS-CoV-2 infection. OR attenuated across the three waves with ranges of 1.08–5.09 in wave 1, 1.06–1.60 in wave 2, and 1.05–1.45 in those not (fully) vaccinated in wave 3. In wave 3, no associations were found for those fully vaccinated. In all waves, the two precarious work dimensions showed weaker or inversed associations. CONCLUSIONS: The COVID-19-JEM is a promising tool for assessing occupational exposure to SARS-CoV-2 and other airborne infectious agents that mainly spread between people who are in close contact with each other. However, its usefulness depends on applied restrictions and the vaccination status in the population of interest.